Paid care worker organizing in England: priorities and progress? - Fisher, Duncan Uist; Foster, Liam (Frontiers in Sociology, 2025)
IntroductionDespite its growth and ubiquity, paid adult social care (ASC) work in England persists as a site of very low pay, insecurity, and exploitation, where ‘decent work' remains elusive. Promoted by a neoliberal agenda focusing on competition and choice, social care provision has developed a quasi-market model. This involves local authorities assessing and commissioning predominantly independent sector providers to deliver care, which relies on outsourcing and contributes to workforce fragmentation. This atomisation, with thousands of providers and many workers employed to support people in their own homes, contrasts with the terrain of more established trade unionism and impedes organizing. Thus far in the English context, however, this phenomenon has received only limited attention in academic research. These challenges within the sector and limited organizing mean that it is important to understand priorities and progress in relation to ASC organizing.MethodsThirty-five semi-structured interviews were conducted with key actors (organizers, administrators, founders) and paid direct care workers involved in organizing in the ASC context in England. Data were examined using thematic analysis.ResultsThe results identify four groupings where paid ASC workers and their representatives seek change: Pay and conditions; Systemic/structural change; Awareness-raising and being heard; and Environment and practices.DiscussionThe discussion assesses the implications of these findings for ASC worker organizing and prospects for change. It contends that there remain significant barriers both to meaningful change in the situation of paid care workers, and to care worker organizing playing a greater or more prominent role in driving change. Concluding reflections consider what the issues identified in care worker organizing reveal about the relative status of care work and the circumstances of care workers, and paid care work's position in contemporary neoliberal capitalism.